Natural Bioactive Compounds Targeting NADPH Oxidase Pathway in Cardiovascular Diseases - Siti Sarah, M Sofiullah; Dharmani, Devi Murugan; Suhaila, Abd Muid; Wu, Yuan Seng *; Sharifah Zamiah, Syed Abdul Kadir; Razif, Abas; Nurul Raudzah, Adib Ridzuan; Mor Hisam, Zamakshashari; Choy, Ker Woon (MDPI, 2023)
Cardiovascular disease (CVD) is the leading cause of death worldwide, in both developed and developing countries. According to the WHO report, the morbidity and mortality caused by CVD will continue to rise with the estimation of death going up to 22.2 million in 2030. NADPH oxidase (NOX)-derived reactive oxygen species (ROS) production induces endothelial nitric oxide synthase (eNOS) uncoupling and mitochondrial dysfunction, resulting in sustained oxidative stress and the development of cardiovascular diseases. Seven distinct members of the family have been identified of which four (namely, NOX1, 2, 4 and 5) may have cardiovascular functions. Currently, the treatment and management plan for patients with CVDs mainly depends on the drugs. However, prolonged use of prescribed drugs may cause adverse drug reactions. Therefore, it is crucial to find alternative treatment options with lesser adverse effects. Natural products have been gaining interest as complementary therapy for CVDs over the past decade due to their wide range of medicinal properties, including antioxidants. These might be due to their potent active ingredients, such as flavonoid and phenolic compounds. Numerous natural compounds have been demonstrated to have advantageous effects on cardiovascular disease via NADPH cascade. This review highlights the potential of natural products targeting NOX-derived ROS generation in treating CVDs. Emphasis is put on the activation of the oxidases, including upstream or downstream signalling events.